PENGARUH PEMBERIAN KOMPENSASI TERHADAP KINERJA KARYAWAN STUDI KASUS PADA AMIK XYZ PALEMBANG - Mulyati Mulyati (Jurnal Informatika Global)
A way a company or personnel department improves job performance, motivation and employee satisfaction is through compensation. Compensation is everything that employees receive as a reward. Compensation is important to employees as individuals because the magnitude of compensation reflects the size of the value of their work among the employees themselves, their families and society. Relative compensation rates indicate their status, dignity and "price". Therefore, when employees consider their compensation is inadequate it will affect job performance, motivation and job satisfaction. The purpose of this study is to know and analyze the effect of compensation on employee performance. The data used in this research are primary data and secondary data. The population of this study were employees of 50 respondents. Data processing with the help of SPSS 15.0 for Windows Software. Data analysis method used is descriptive quantitative by using multiple linear regression. The result of the research on the regression equation obtained is Y = 10.166 + 0.391X, it shows that compensation has a significant effect on employee performance. The value of r obtained by 0.534 means that the relationship between the two variables is positive and strong enough. And from t test known that r is significant because t count (4.373)> t table (2.021). This means that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. Employee perceptions regarding the compensation received by employees so far have a positive and significant impact on employee performance Keywords:Compensation, Performance, SPSS.